1997
DOI: 10.1097/00007632-199712150-00021
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Effects on the Lumbar Spinal Canal

Abstract: Axial loading of the lumbar spine in computed tomographic scanning and magnetic resonance imaging is recommended in patients with sciatica or neurogenic claudication when the dural sac cross-sectional area at any disc location is below 130 mm2 in conventional psoas-relaxed position and when there is a suspected narrowing of the dural sac or the nerve roots, especially in the ventrolateral part of the spinal canal in psoas-relaxed position. The diagnostic specificity of the spinal stenosis will increase conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 178 publications
(37 citation statements)
references
References 12 publications
3
34
0
Order By: Relevance
“…This study confirmed what several other studies already have shown, that the available space within the lumbar spinal canal varies depending on the loading conditions of the spine [2,12,17]. By quantifying separately each structure's contribution to the reduction of the size of the spinal canal in the unloaded and loaded spines (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This study confirmed what several other studies already have shown, that the available space within the lumbar spinal canal varies depending on the loading conditions of the spine [2,12,17]. By quantifying separately each structure's contribution to the reduction of the size of the spinal canal in the unloaded and loaded spines (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Axial loading of the spine Axial loading of the spine was performed using a non magnetic compression device and a harness (DynaWell, DynaMed AB, Stockholm, Sweden) [17]. When loaded the patient was lying supine with extended hips and knees.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations